Technical comparison of MinIon and Illumina technologies for genotyping Chikungunya virus in clinical samples - Leandro Menezes de Souza; Isabelle Dias de Oliveira; Flávia Cristina Silva Sales; Antonio Charlys da Costa; Karoline Rodrigues Campos; Adriano Abbud; Juliana Mariotti Guerra; Cinthya dos Santos Cirqueira Borges; Carlos Pires Fernandes Júnior Takahashi; Leonardo José Tadeu de Araújo (Journal of Genetic Engineering and Biotechnology, 2023)
Abstract New-generation sequencing (NGS) techniques have brought the opportunity for genomic monitoring of several microorganisms potentially relevant to public health. The establishment of different methods with different mechanisms provides a wide choice, taking into account several aspects. With that in mind, the present aim of the study was to compare basic genomic sequencing metrics that could potentially impact genotyping by nanopores from Oxford Nanopore Technologies and by synthesis from Illumina in clinical samples positive for Chikungunya (CHIKV). Among the metrics studied, running time, read production, and Q score were better represented in Illumina sequencing, while the MinIOn platform showed better response time and greater diversity of generated files. That said, it was possible to establish differences between the studied metrics in addition to verifying that the distinctions in the methods did not impact the identification of the CHIKV virus genotype.